YY Geminorum: A very late type close binary with possible magnetic stellar wind - Qian S. (2014)
The O-C curve of the very late type close binary (dM1e + dM1e) YY Geminorum is formed and analyzed based on all available times of minimum light. It is found that the orbital period shows a secular decrease with rate dP/dt = -1.08 × 10-8 days yr-1. There is weak evidence indicating that a small-amplitude period oscillation is superposed on the period decrease. YY Gem is a well-detached eclipsing binary containing two very active components. The secular period decrease may suggest that the system is undergoing secular mass and angular momentum loss via a magnetic stellar wind. If the small-amplitude oscillation is real, it can be explained either by magnetic activity cycles or by the presence of a giant planet or brown dwarf.